Electromyographic activity and applied load during high intensity elastic resistance and nautilus machine exercises - Aboodarda, S.J.; Shariff, M.A.H.; Muhamed, A.M.C.; Ibrahim, F.; Yusof, A. (2011)
This study was designed to quantify and compare Electromyographic activity (EMG) and applied load in quadriceps muscle within performing high intensity knee extension exercises by Elastic Resistance (ER) and Nautilus Machine (NM). Sixteen male and female subjects (22.4 Â± 4.7 yrs) completed 8 RM seated knee extension by NM, elastic tubing with original length (E0) and elastic tubing with 30 decrement of original length (E30). The mean value of EMG and external force were calculated and synchronized across various segments of motion for the three modes of training. The results demonstrated that in the early concentric and late eccentric segments of contraction, NM elicited significantly higher muscle activation than both E30 and E0 (p < 0.05). However, in the mid-concentric and mid-eccentric as well as late concentric and early eccentric segments no significant differences were observed between NM and E30. These findings supported the approach that developing external recoil of force in ER device by reducing 30 of initial length of elastic material can offer similar neuromuscular activation compared with NM. On this basis, E30 can be suggested as an affordable and non-gym based exercise device which has the capacity to provide an appropriate high resistance stimulus to meet the training requirement of athletes. Â© Editorial Committee of Journal of Human Kinetics.